The Multiplicity And Probability Of Meanings In The Prophetic Hadith: A Study In Linguistic, Rhetorical, And Da‘wah Aspects/ التعدد والاحتمال لمعاني الحديث النبوي الشريف: دراسة دعوية لغوية بلاغية - Alharbi, Mohammed Fahad; Ahmed Fath El-Bab, Mohamed Salah El-Din; Mohamed Salem, El Sayed Binti; Nasirudeen, Abdulwasiu Isiaq (Ijaz Arabi Journal of Arabic Learning, 2025)
The simplicity of many Islamic laws is not a fabrication of jurists, but rather a deduction from the meaning of Islamic texts. These jurists cannot achieve such an understanding without grasping the nuances of the Arabic language and its rhetoric, which are essential to comprehending Arabic texts in general and Islamic texts in particular. This study highlights the differences between schools of thought and individuals in their understanding of Arabic texts. The diversity and probability of interpreting Qur'anic and Sunnah texts on principles established by scholars of Usul al-Fiqh (the principles of Islamic jurisprudence). Precise scholarly standards govern these differences. This study also aims to demonstrate that diversity and probability in interpreting Arabic texts have practical applications in da'wah (Islamic outreach). The researchers employed a variety of overlapping methodologies throughout the research process, including an inductive method; the analysis was carefully selected from reliable sources within established Sunni schools of thought. This selection process was not comprehensive but rather selective, focusing on elements clearly aligned with the research objectives. Understanding jurisprudential issues and uncovering their depth requires linguistic and rhetorical analysis of Arabic texts, using appropriate tools. This process necessitates consulting the works of scholars, including linguists, jurists, commentators, and hadith scholars. Without this, researchers cannot fully grasp the intended meaning of the texts. Furthermore, this research confirms that the study of Islamic sciences cannot be separated from the study of linguistics.